Three dimensional acoustic tweezers with vortex streaming - Li, Junfei (2021)
Acoustic tweezers use ultrasound for contact-free manipulation of particles from millimeter to sub-micrometer scale. Particle trapping is usually associated with either radiation forces or acoustic streaming fields. Acoustic tweezers based on single-beam focused acoustic vortices have attracted considerable attention due to their selective trapping capability, but have proven difficult to use for three-dimensional (3D) trapping without a complex transducer array and significant constraints on the trapped particle properties. Here we demonstrate a 3D acoustic tweezer in fluids that uses a single transducer and combines the radiation force for trapping in two dimensions with the streaming force to provide levitation in the third dimension. The idea is demonstrated in both simulation and experiments operating at 500 kHz, and the achieved levitation force reaches three orders of magnitude larger than for previous 3D trapping. This hybrid acoustic tweezer that integrates acoustic streaming adds an additional twist to the approach and expands the range of particles that can be manipulated.